Molecular detection of iron gene on multidrug resistant avian fecal Escherichia coli isolated from broiler on traditional markets, Surabaya, Indonesia - MARIANA FEBRILIANTI RESILINDA PUTRI; IRFAN ALIAS KENDEK; FRESHINTA JELLIA WIBISONO; MUSTOFA HELMI EFFENDI; DADIK RAHARDJO; WIWIEK TYASNINGSIH; EMMANUEL NNABUIKE UGBO (Society for Indonesian Biodiversity, 2023)
Abstract. Putri MFR, Kendek IA, Wibisono FJ, Effendi MH, Rahardjo D, Tyasningsih W, Ugbo EN. 2023. Molecular detection of iron gene on multidrug resistant avian fecal Escherichia coli isolated from broiler on traditional markets, Surabaya, Indonesia. Biodiversitas 24: 6454-6460. Avian Fecal Escherichia coli (AFEC) is the cause of colibacillosis, which often infects the poultry industry throughout the world. The virulence gene influences the iroN factor, which causes systemic infections in poultry. This research aimed to determine Multidrug Resistance (MDR) in AFEC obtained from traditional markets in Surabaya. There were 96 cloacal swab samples from broiler chickens. The samples were isolated and identified using culture media in the form of Eosin Methylene Blue Agar (EMBA), gram stain, Triple Sugar Iron Agar (TSIA), Sulfide Indole Motility (SIM), Simmons Citrate Agar (SCA), Voges Proskauer (MR-VP) indole and methyl test; detection of multidrug resistance using Mueller-Hinton Agar (MHA) media. The results of the isolation and identification of Escherichia coli bacteria in this study showed that 60.4% of the isolates were positive for Escherichia coli. Escherichia coli is resistant to tetracycline antibiotics by 56%, ciprofloxacin by 55%, antibiotics aztreonam 29%, kanamycin 20%, and chloramphenicol 18%. The multidrug resistance test result on Escherichia coli was 25.8%. The PCR test results for the iroN gene were 40%. Therefore, there are MDR and iroN genes in avian fecal Escherichia coli in Surabaya traditional markets; APEC with iroN gene poses the potential to affect public health.